2003
DOI: 10.1016/s0168-1605(03)00085-0
|View full text |Cite
|
Sign up to set email alerts
|

Black Aspergillus species as ochratoxin A producers in Portuguese wine grapes

Abstract: To evaluate the incidence of fungi producing ochratoxin A (OA) in Portuguese wine grapes, a survey was conducted in 11 vineyards, from four winemaking regions each with distinct climatic conditions. From setting to the harvesting period, a total of 1,650 berries were sampled by plating methods. Out of 370 aspergilli and 301 Penicillium strains isolated, 14% of the aspergilli were OA-producing strains. None of the penicillia were OA-producing strains. The black aspergilli were predominant (90%). All Aspergillus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
129
2
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(143 citation statements)
references
References 19 publications
9
129
2
2
Order By: Relevance
“…It has been suggested that A. carbonarius could be the major cause of OTA production in grapes and derivatives (Cabañes et al, 2002) mainly in the Mediterranean region (Serra et al, 2003), and that A. ochraceus could be the main source of OTA in coffee (Logrieco et al, 2003;Taniwaki et al, 2003). The aim of the present study was to identify the contaminate species of Aspergillus found inside of coffee beans.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It has been suggested that A. carbonarius could be the major cause of OTA production in grapes and derivatives (Cabañes et al, 2002) mainly in the Mediterranean region (Serra et al, 2003), and that A. ochraceus could be the main source of OTA in coffee (Logrieco et al, 2003;Taniwaki et al, 2003). The aim of the present study was to identify the contaminate species of Aspergillus found inside of coffee beans.…”
Section: Discussionmentioning
confidence: 93%
“…Such studies involve RFLPs of both nuclear and mitochondrial DNA, polymerase chain reaction (PCR)-based methods and phylogenetic analysis (Abarca et al, 2004;Geiser et al, 2007;Perrone et al, 2007;Samson et al, 2007). Furthermore, some black Aspergillus species have been described recently, for instance A. brasiliensis (Varga et al, 2007), A. ibericus (Serra et al, 2003), A. uvarum (Perrone et al, 2008), andA. vadensis (de Vries et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The mycoflora of raisins was determined as described (Serra, 2003). A total of 10 raisins of each sample were planted in the medium Dichloran RoseBengal chloramphenicol (Oxoid CM727) and were incubated at 25 ° C in darkness for 1 week.…”
Section: Materials and Methods Samplesmentioning
confidence: 99%
“…japonicus is also occasionally isolated from grapes, but its production ability in vitro has not been demonstrated yet [12,15,17,24]. A. uvarum is also an uniseriate species that is included in Aspergillus section Nigri that has been reported to occur in grapes in Mediterranean countries but any isolate has been described as OTA producer [34].…”
Section: Introductionmentioning
confidence: 99%